Perkembangan Akuntansi Pemerintah Dalam Implementasi Standar Akuantansi Pemerintah Di Kementrian Sosial - Saridawati Saridawati; Lathifah Dinar; Zahra Nur Aziza; Anindya Putri Widasari; Nita Tri Handayani (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
This study analyzes the development of the government accounting system in Indonesia, focusing on the transition from the cash basis to the accrual basis, which began with the implementation of Government Regulation No. 24 of 2005 and was later replaced by Government Regulation No. 71 of 2010 on Government Accounting Standards (SAP). Through a literature review approach, this Study identifies the development trends and outcomes of applying the accrual basis for accounting in order to improve transparency and accountability in public financial transactions. As a case study, the Ministry of Social Affairs of the Republic of Indonesia (Kemensos) was selected to illustrate the implementation of SAP, including the preparation of the cash-based Budget Realization Report (LRA) as well as other accrual-based financial statements. The results show that accrual-based accounting is an important factor in improving transparency and accountability in government financial reporting.